2012
DOI: 10.1021/ma202721s
|View full text |Cite
|
Sign up to set email alerts
|

Triggering Polymeric Nanoparticle Disassembly through the Simultaneous Application of Two Different Stimuli

Abstract: Polymeric nanoparticles whose disassembly into their component polymer chains is triggered by the simultaneous application of two different stimuli are described. Reversible addition–fragmentation chain transfer (RAFT) polymerization was utilized to prepare acrylamide-based linear copolymers displaying pyridyl disulfide appendages and either aldehyde or amine functional groups. These copolymer chains were intermolecularly cross-linked through imine bond formation at pH 8.0 and then through disulfide bond forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 43 publications
1
85
0
Order By: Relevance
“…44 In this paper, polymeric nanoparticles were prepared by cross-linking aldehyde/disulfide-functionalized copolymers and amine/disulfide-functionalized copolymers (Figure 3) through the formation of benzoic imine and disulfide bonds. It is reported that the benzoic imine bond is stable at pH 7.4 but hydrolyzes in an acidic environment.…”
Section: Chemical-chemical Dual Stimuli-responsive Macromoleculesmentioning
confidence: 99%
“…44 In this paper, polymeric nanoparticles were prepared by cross-linking aldehyde/disulfide-functionalized copolymers and amine/disulfide-functionalized copolymers (Figure 3) through the formation of benzoic imine and disulfide bonds. It is reported that the benzoic imine bond is stable at pH 7.4 but hydrolyzes in an acidic environment.…”
Section: Chemical-chemical Dual Stimuli-responsive Macromoleculesmentioning
confidence: 99%
“…Two copolymers, an aldehyde/disulfide-functionalized copolymer (P1) and an amine/disulfide-functionalized copolymer (P2b), were synthesized as the building blocks to form core crosslinked star (CCS) polymers. 76 To further decorate the CCS polymer, hydrazide end-functionalized poly(ethylene glycol) was synthesized, which could assemble with the CCS polymer based on the formation of a hydrazone bond (Fig. 13).…”
Section: Schiff-base Linker Outside Polymer Main Chainmentioning
confidence: 99%
“…Thus, polymerization of monomers M1-M3 in a molar ratio of 1 : 1 : 8 was performed as previously reported, 22) with changes in the monomer with disulfide functionality (M2), which in this work was an acrylate instead of an acrylamide, to obtain the desired polymer P1. Size exclusion chromatography analysis (SEC) of P1 afforded one peak with an average molecular weight (M w ) of 12500 g/mol and a polydispersity index of 2.3.…”
Section: S-1-dodecyl-s′-(αα-dimethyl-α″-aceticmentioning
confidence: 98%
“…[34][35][36] As a matter of fact, this polymer has been used in a wide variety of systems where it has been successfully combined with synthetic polymers having as a result the improvement of various mechanical and biological properties. 37,38) In line with the work of Jackson and Fulton, 22) we wish to report here the synthesis of a a new stimuli-sensitive nanostructured system in which one of the polymeric acrylamide subunits is replaced by thiolate chitosan of semisynthetic origin in order to have a potentially biocompatible material as part of the structural base of the nanoparticles. In addition, the material response towards pH and redox potential stimuli is reported.…”
mentioning
confidence: 92%
See 1 more Smart Citation